PERKEMBANGAN FISIK DAN SOSIO - EMOSI PADA SISWA DENGAN GEJALA FOBIA SPESIFIK : STUDI KASUS PADA SISWA DENGAN GEJALA FOBIA NASI - Karimatus Saidah (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2016)
Phobia according to the view of the theory ofPsychoanalysis of Freud is self-defense to counter fears that inproduction forced by the id impulses. Phobias against rice canbe so will affect the physical conditions. On the other hand, thephobia of rice can also affect socio emotions. This research isconducted to find out how the physical development and socioemotional of student on grade V SD with the symptoms ofspecific phobias against rice. This research use the qualitativeapproach, which a greater emphasis on the phenomenon ofexisting problems in the field. The model used in this study is amodel case study. Participants in this study have symptoms ofphobia against rice, he dodged if there is rice in the vicinity andangry if there is rice stuck to his body. Phobias against rice notto disturb its physical development. Phobias of rice affects thedevelopment his temper only when he is confronted bycircumstances related to the rice that is shows reactions avoidand angry.